El desarrollo personal y profesional mediante el aprendizaje reflexivo. Una experiencia en el grado de Educación Social. - Judit Fullana Noell; Maria Pallisera Díaz; Josep Miquel Palaudàrias Martí; Mercè Badosa (Universitat Politècnica de València, 2014)
In the last years, an increase of the interest to develop educational practices in higher education, based on the approach of the reflective learning, is observed. Nevertheless, we scarcely find in our context researches or experiences that allow knowing students' perceptions about this teaching and learning approach. We have developed an experience in the bachelor of Social Education at the University of Girona with the aim to contribute to the personal and professional development of future social educators in their initial training, using reflective learning methodology. In this article we present an evaluation of the experience based on students' perceptions. They assessed the usefulness they think the module has for their training, the methodology and the activities. This evaluation has been carried out through in-depth interviews to 17 students who participated in the module in 2010-11 academic year. The results show that students assess positively the experience, either its general usefulness or the methodology of reflective learning, although they acknowledge some difficulties to carry out such a process which involves a high degree of introspection and a difficulty to set the boundaries in the narration of personal questions. The study also shows some challenges related on the need, but also the difficulty, to include personal and professional development as a powerful axis in the higher education curriculum, as well as elements linked to reflective learning assessment.